Residential mobility of the European elderly - Viola Angelini; Anne Laferrère (Center for Economic Studies and ifo Institute (CESifo), 2010)
With the ageing of the European population, the housing choices of the elderly will have consequences on the whole housing market. In this paper we use data from the first two waves of the Survey of Health, Ageing and Retirement in Europe (SHARE) to analyse the residential mobility decisions of the elderly and the factors influencing them in eleven European countries.
Keywords: D10; R21; R28; 330; housing; ageing; residential mobility; housing policy; Wohnstandort; Alte Menschen; Wohnungspolitik; Wirkungsanalyse; Europa